Pengembangan permainan woodball: Model alternatif pembelajaran pendidikan jasmani pada permainan bola kecil - Adi Susanto, Damar; Herlambang, Tubagus; Kresnapati , Pandu (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2022)
Woodball games have not been taught in small ball material in schools. The purpose of this study was to produce a woodball game model as an alternative to physical education learning at SMP Negeri 2 Kendal. This research refers to the development model of Borg & Gall. Data collection techniques used in the study were observation, questionnaires and documentation. The subjects in this study were students of class XI A and XI B. The data analysis technique was quantitative descriptive method in the form of percentages, while the data in the form of suggestions and reasons for choosing answers were analyzed using qualitative analysis techniques. Scores of assessment results from experts and students will then be categorized by the percentage formula. The results of the small-scale field trial obtained that the average percentage of the appropriate answer choices was 78.3% (good). Meanwhile, for large-scale field trials, expert evaluation results were obtained, namely, 85% (good) physical education experts, 85% (good) woodball learning experts. From the large-scale field trial, it was found that the average percentage of the correct answer choices was 84.5%, and it met the criteria for good. So, the product of developing a small wooden ball game can already be used for students. Based on the research data, the woodball small ball game model is feasible to use and can be used as an alternative reference for small ball game material.